Re-defining `good business' in the face of Asian drivers of global change: China and the global corporate social responsibility discussion - Jochen Weikert (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
The legitimacy of business action in globalisation poses a challenge for the emerging global governance architecture. For some time already, issues around business legitimacy have been discussed – although less so in scientific debates – under the header `corporate responsibility' (`corporate social responsibility, `corporate citizenship' etc.). However, these discussions are subject to comprehensive global change. And important agents of the current dynamics of global change originate in the `Asian Drivers' countries India and China. The future global business legitimacy discussion will be Indian and be Chinese to a much higher degree than most expect today. And today's global crises, perceived by many as a failure of the western institutions of capitalism, catalyse this process. This study observes China. It looks at the Chinese models of legitimizing business action from the angle of the so far dominant OECD-led debate: is there significant variation between the practices of OECD and Chinese actors? What is the impact of the interaction between the OECD's and Chinese types of business legitimization on the global discussion?
Keywords: 650; Corporate Social Responsibility; Unternehmensethik; Globalisierung; Multinationales Unternehmen; Asien; China